مسؤولية السلطة التنفيذية في النظام الدستوري للولايات المتحدة الأمريكية - عباس، كاظم علي Abbas, Kazem Ali (الجامعة المستنصرية - كلية القانون, 2010)
In principle, the presidential system is mainly based on the total or absolute separation of powers, then the legislative authority is specialized in the matters of legislation, while the executive branch, mainly the head of state, is specialized in the matters of implementation of laws, then the judicial's power lies with settling disputes . \ \ separation of powers in its strict meaning prohibit any kind of collaborative relationship or control between them, which achieves to each authority its private existence and autonomy of all other authorities. \ \ However, this theoretical reality of presidential system did not find its fully application in the Constitution of the United States of America, the home country for this system. The provisions of this Constitution identified with evolving norms relating to its application, during the two centuries of the American presidential system characters .One of which is the relations of the three authorities.
Keywords: السلطة القضائية -- الولايات المتحدة الأمريكية -- الدساتير -- السلطة التنفيذية -- القوانين والتشريعات -- الملوك والحكام -- الحصانة القضائية